Reproduksi Hemiptarsenus varicornis (Hymenoptera: Eulophidae) : pengaruh ketinggian tempat, suhu dan tanaman inang terhadap keperidian - Reflinaldon Reflinaldon; Mardinus Mardinus; Dwinardi Apriyanto (Perhimpunan Entomologi Indonesia, 2007)
H. varicornis is a larval parasitoid of leafminer distributing and associating with several host plants in highland vegetables planting. Three experiments were conducted to study effects of elevations, temperatures and host plants on female reproduction fitness. The first experiment, we compared fitness traits of female originated from different elevation areas i.e Pandai Sikek (900-1000 m above sea level ), Alahan Panjang(1200-1300m) and Kayu Aro (1400-1500m) whilst two other experiments were treatment of temperatures level (18, 23, 280C), and host plants (red bean, bean and cucumber) to investigate longevity, egg layed, survivorship. Parasitoids originated from Kayu Aro showed the highest longevity and number of eggs. The best fitness also was performed when adult female maintained at 230C. Parasitism, superparasitism and paralization of the parasitoid have been discussed in this paper.